The Effect of Influencer Credibility Attributes and Social Media Content Attributes on Purchase Intention With Brand Image as A Mediating Variable: A Study of Local Cosmetic Consumers in Jakarta - Dini Indriyani; Alfatih Sikki Manggabarani (Cerdika: Jurnal Ilmiah Indonesia, 2026)
This study examines the effects of influencer credibility attributes and social media content attributes on purchase intention, with brand image as a mediating variable, in the context of local cosmetic products in Jakarta. Using a quantitative approach with Structural Equation Modeling–Partial Least Squares (SEM-PLS), data were collected from 250 respondents through an online survey. The results show that influencer trustworthiness and expertise significantly influence brand image and purchase intention, whereas attractiveness affects purchase intention only through brand image. Informative and interactive social media content positively impacts brand image and purchase intention, whereas entertainment-oriented content does not show a significant effect. Brand image is confirmed as a key mediating mechanism that strengthens the relationship between influencer credibility, content attributes, and purchase intention. These findings highlight the importance of credibility-driven influencers and informative, interactive content strategies in enhancing consumer purchase intention in the cosmetic industry.